Secondary electron emission characteristics of alumina coating on metallic substrate prepared by atomic layer deposition. (1st February 2023) - Wei, Wenlu; Yan, Baojun; Heng, Yuekun; Liu, Shulin; Zhang, Binting; Peng, Huaxing; Wang, Yuman; Wen, Kaile
Abstract: The main objective of this study is to research the secondary electron emission characteristic of different thickness alumina coatings which are prepared by atomic layer deposition (ALD) technique on several metallic secondary-emitting materials. The experimental results reveal that secondary electron yield (SEY) property concerned with the metal work function and the surface topography of alumina coatings when coating thickness is in the nanometer level. In addition, after utilizing SEY measurement setup and pulsed electron gun, the SEY curves of metallic substrates with different thickness alumina coatings and primary energy (PE) of incident electron could be measured. From an analysis of the SEY curves, some key parameters related to secondary electron emission characteristics such as the maximum SEY value and its corresponding PE of incident electron, and the penetration depth of incident electron can be obtained. Furthermore, basing on the ALD technique and on the SEY results of stainless steel substrate coated with 80-cycle alumina thin film, a novel 18-stage discrete dynode electron multiplier (DDEM) was fabricated and tested. The gain of DDEM 1.6× 10 6 was obtained.